PERAQ API TRADITION N LOMBOK: A BOURDIEU PERSPECTIVE REVIEW - Zuhriah, Nur Azizah; Warto, Warto; Pitana, Titis Srimuda (Humaniora, 2020)
The research aimed to dismantle the meaning of peraq api in its social practices involving habitus and the field in Sasak cosmology. Pierre Bourdieu?s social practice theory was used as an analysis to uncover the meanings built in the tradition of the peraq api. The meaning of peraq api in its social practice was discussed using qualitative methods and interpretative descriptive data analysis techniques and using a hermeneutic approach. The results of this research indicate that the tradition of peraq api is a manifestation of life that represents the creation of beings. This happens because the attitude and perspective of Sasak society about nature originated from the monotheism?s cosmology. This perspective gives rise to behavior to maintain the cosmological balance. Tawhid is a general view of reality, truth, the world, space and time, and human history, which is represented through the tradition of the peraq api.